ANALISIS KELAYAKAN BUKU TEKS PELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN KELAS VII KURIKULUM 2013 - Hidayatul Wakhidah (JURNAL TEMATIK, 2014)
This study is aimed to describe the feasibility of civics textbook for seventh grade in Curriculum 2013 in terms of aspect of the content/ material, the presentation based on a scientific approach, the presentation based on an authentic assessment, language, and graphic and also factors cause of publication of civics textbook which has not appropriate with the demands of Curriculum 2013. The problems is discussed in this study are how feasibility of civics textbook for seventh grade in Curriculum 2013 reviewed by those various aspects. This study is a descriptive content analysis. Samples were taken by purposive sampling technique which is civics textbook for seventh grade in Curriculum 2013. Data was collected by questionnaire, documentation, interviews, and literature technique. Data were analyzed by descriptive statistical techniques, statistical hypothesis with one sample t test, and analysis of qualitative. The results showed: (1) some aspects of the content / material in the textbook are still in need of improvement, (2) textbooks generally has not enough to encourage the learning activities carried out by the scientific approach, (3) component of authentic assessment has been accommodated in the book, (4) some aspects of language are still need of improvement, (5) some aspects of the graphics are still need of improvement, (6) the factors that cause the emergence in the problem of the book are compilation of the textbook is still trapped on cognitive aspects, civics used as a tool to perpetuate power, and the difficulties to implement book valuation with multilevel mechanism. The conclusions acquired in this study are: (1) aspects of conformity contents/ materials and participation skills have not complied the feasibility standards, while civic knowledge, intellectual skills, and civic dispositons have complied the the feasibility standard, (2) aspects of the scientific approach has not complied the feasibility standard, (3) aspects of authentic assessment has complied the feasibility standard, (4) aspects of language has not complied the feasibility standard, (5) aspect of graphics has not complied the feasibility standard, and (6) the factors that cause the emergence in the problem of the book are compilation of the textbook is still trapped on cognitive aspects, civics used as a tool to perpetuate power, and the difficulties to implement book valuation with multilevel mechanism